Differing Strategies Despite Shared Lineages of Motor Neurons and Glia to Achieve Robust Development of an Adult Neuropil in Drosophila. - Enriquez, J.; Rio, L.Q.; Blazeski, R.; Bellemin, S.; Godement, P.; Mason, C.; Mann, R.S. (Neuron, 2018)
In vertebrates and invertebrates, neurons and glia are generated in a stereotyped manner from neural stem cells, but the purpose of invariant lineages is not understood. We show that two stem cells that produce leg motor neurons in Drosophila also generate neuropil glia, which wrap and send processes into the neuropil where motor neuron dendrites arborize. The development of the neuropil glia and leg motor neurons is highly coordinated. However, although motor neurons have a stereotyped birth order and transcription factor code, the number and individual morphologies of the glia born from these lineages are highly plastic, yet the final structure they contribute to is highly stereotyped. We suggest that the shared lineages of these two cell types facilitate the assembly of complex neural circuits and that the two birth order strategies-hardwired for motor neurons and flexible for glia-are important for robust nervous system development, homeostasis, and evolution.